Middle East and North Africa Local Service Delivery Initiative : Promoting Social Accountability and Demand for Good Governance - Beddies, Sabine; Felicio, Mariana; Dedu, Gabriel; Fall, Fatou; Vagneron, Caroline (Washington, DC: World Bank, 2012)
Good governance is an underlying condition for the formulation of effective and efficient public policies, programs, and services. It implies a social contract and adherence to rules and laws that enable improved interaction between government and constituents on transparency, accountability, and participation. Good governance is equitable and inclusive, responsive and consensus-oriented. Governance reforms rank high on the development agenda of many Middle East and North Africa (MENA) countries, particularly in regard to public service delivery. Social accountability approaches aim to improve the performance of public services, user satisfaction, and value for money. This note highlights lessons learned thus far from the four Local Service Delivery Initiative (LDSI) pilot programs.